An Analysis of Hydraulic Properties of Soil Based on Soil Texture in Chiti Areas of Lamjung District In Nepal (Geographical Journal of Nepal, 2018)
Soil hydraulic properties play crucial role for having sustainable growth of vegetation and also required for carrying out environmental studies especially subsurface ground water. Since, its direct measurement is time consuming and therefore costly, indirect methods such as pedotransfer functions have been used to estimate hydraulic properties. Soil hydraulic properties: bulk density, available water, permanent wilting point, field capacity and water retention capacity and saturated hydraulic conductivity are essential to be studied. These factors affect soil productivity and the environment. The knowledge of soil water properties for different land-use and land cover types based on soil textural classes are important for re-growth of plants and agriculture crops and ultimately efficient soil and water management. The aim of this paper is to measure soil hydraulic properties based on soil textural classes for different land use types. Furthermore, the use of the soil texture triangle: hydraulic properties calculator has been assessed. The comparison of the soil hydraulic properties obtained from textural triangle for different land use land and cover types has also been analyzed. Moreover, an analysis of variance (ANOVA) of soil hydraulic properties among different land use types has been performed. The soil reaction (pH) value ranges from 4.69 to 6.69 and as a mean of 5.51 indicating slight acidic. The analysis showed barren land occupying 14.3 percent of total land use/land cover is found to be suitable for plant growth since it has loam texture having bulk density less than 1.6 g/cm3.The analysis of bulk density showed that barren land is significantly different at the 0.05 level from both agriculture and forest, whereas agriculture and forests  are not different even at 0.05 significant levels. It verifies the fact that mean bulk density at the depth of 0.15 cm is affected by land use land cover types.The Geographical Journal of NepalVol. 11: 63-76, 2018